Tipologi Fasad Bangunan Quonset Hut di Kota Balikpapan - Mallika Putri Santoso (Arsir: Jurnal Arsitektur, 2026)
Quonset Hut is a semi-permanent prefabricated building with a light steel structure and a curved corrugated roof, designed by the United States military during World War II as a barracks and storage warehouse. Although initially temporary, this building still survives in various countries, including Indonesia. In Balikpapan, Quonset Hut is known as "Rumah Lengkung" and has been designated as a cultural heritage building, although now only 7 out of 8 units remain due to minimal attention to its historical and architectural value. This study aims to document the typology of Quonset Hut facade elements in Balikpapan with a qualitative descriptive approach using Moneo's typology theory (1978). Data were obtained through interviews, field observations, and literature and document studies. The results of the study indicate that the typology of the facade can be categorized based on the type of building and its constituent elements. Based on the type of building, there are three main types, namely Redesain 24 'x 36' Hut (1941), U.S. Navy Steel Arch Rib Hut 20' x 56' (1944), and U.S. Navy Steel Arch Rib Hut 40' x 100' (1944). Meanwhile, based on the facade elements, 10 types of doors, 12 types of windows, 4 types of front walls, 4 types of side walls, 2 types of roofs, and sun shading elements consisting of 2 types of overhangs, 6 types of canopies, and 1 type of double façade were found. These findings reveal the diversity of forms, materials, and orientations, but still maintain the distinctive character of the Quonset Hut as an iconic historical heritage building.